VRIO Analysis as a Basic Strategy for Obtaining Construction Tenders in Construction Service Companies - Wulandari, Cresentiana Cythia; Agustini, Maria Y. D. Hayu (Journal of Management and Business Environment (JMBE), 2024)
This research is related to the condition of PT XY which has not been able to reach the target to get a construction tender. The aim of this research is to determine the right strategy in obtaining construction tenders based on the results of an analysis of internal conditions using VRIO analysis. The object of research is the strategy to obtain a construction tender for PT XY, a private construction service company with a "Large" qualification located in Central Jakarta. The research method uses a qualitative descriptive analysis. Data collection techniques with interviews and documentation. The analysis tool used is VRIO. Based on the results of the VRIO analysis, the company has a sustainable competitive advantage in the company's financial resources, reputation, innovation and capabilities. While technology and physics are in the category of temporary competitive advantage. Human resources fall into the category of competitive parity. The results of this study are priority strategies for obtaining construction tenders, namely employee recruitment, increasing employee competence and abilities, and conducting a winning analysis.